Effect of cumulative time of Helicobacter pylori infection on gastric precancerous lesions? - Coşar, Arif Mansur (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Coşar AM. Effect of cumulative time of Helicobacter pylori infection on gastric precancerous lesions? Turk J Gastroenterol 2018; 29: 524-5.